Practitioner auto-ethnography: self-reflection for discovery and deeper understanding. Issue 3 (1st September 2020) - Slade, Dennis; Martin, Andrew; Watson, Geoff
ABSTRACT: An auto-ethnographic approach to framing and discussing issues has provided sport and physical education (PE) scholars with a method to capture their perspectives, ways of knowing relative to issues, and to solve problems in various contexts. However, the processes for achieving these self-reflective insights have been at the behest of the judgement of the individual authors rather than a shared generic process. This paper presents a generic self-reflective model as a potential shared framework that practitioners in sport and PE might employ to seek resolutions and in-sights into issues within their disciplines. The model is illustrated through referencing the lead author's reflections about their teaching practice and place within the development of Game Centred Learning (GCL) and Teaching Games for Understanding (TGfU) in New Zealand, 1969-2019. This reflective process is achieved through an emergent, evolving continuum of life-story biography, evocative auto-ethnography and analytical auto-ethnography.